Undergeraduates’ Awareness Of And Readiness To Adopt Augmented Reality Applications For Learning In University Of Ilorin, Ilorin, Nigeria - Babalola Ebenezer Omolafe; Issa Ahmed Idris; Aladesusi Gboyega Ayodeji; Omolafe Eyiyemi Veronica; Ibraheem Faidat Omolara; Nuhu Kehinde Muritala (STKIP Rokania Pasir Pangaraian, 2021)
ABSTRACT Augmented Reality (AR) is one of the emerging technologies which allow the co-existing of physical and virtual objects and support real time interaction. Augmented reality consists of merging live images with virtual layers of information. These layers of information consist of three-dimensional (3-D) models that include content, images, sounds, and videos. In addition, AR has been defined as a real time direct or indirect view of a physical real world environment that has been enhanced by adding virtual computer generated information to it. This study assessed undergraduates’ awareness and readiness to adopt augmented reality applications for learning in University of Ilorin, Nigeria. The study adopted descriptive research design of the survey type. A researcher-designed instrument was used to elicit responses from one hundred and sixty (160) undergraduates. Answers were provided to two research questions and one research hypotheses were tested at 0.05 level of significance. The findings of this study revealed that many undergraduates claimed that they have heard of augmented reality and its applications for learning. Undergraduates are ready to adopt augmented reality applications for learning. No significant differences in the male and female readiness to adopt augmented reality applications for learning. The study concluded that undergraduates’ readiness to adopt augmented reality applications for learning is high and so is their awareness of augmented reality applications for learning. AR will change the traditional classroom setting of one on one teaching to virtual learning. Thus, the study recommended that students should be encouraged to utilize more augmented reality applications thereby giving them more awareness of its wide range of applications.